Evaluation of Pedulilindungi Applications in the Jabodetabek Region - Kevin Kevin; Riyanto Jayadi (Journal of Economics and Business UBS, 2023)
This paper will explain the result of evaluation using combination between technology acceptance model (TAM) and updated DeLone and McLean IS success model. The objective of this research is to analyze correlation between system quality, information quality, service quality, perceived risk, attitude, and actual use in moderation of age which is the factor influencing technology acceptance model of PeduliLindungi. The method of research is to analyze the relationship between variable stage before. The data collection techniques used in this paper is using questionnaire and Likert scale. The data analysis method in this study uses partial lease square (PLS) to do validity test, reliability test and hypothesis analysis. The result of this paper is the technology acceptance model of PeduliLindungi which has strong influence to increase users’ attitude that would increase users actual use.